An estimation of 2DEG density for GaN HEMT using analytical equation considering the charge conservation low. (February 2022) - Al-Saman, Amgad A.; Ryndin, Eugeny A.; Pei, Yi; Lin, Fujiang
Highlights: An analytical physical-based model for electron concentration in GaN HEMT. The model considers the charge conservation law and positive charge in channel. The model in excellent agreement with the numerical data. Abstract: An analytical physics-based model for 2DEG density estimation in the GaN HEMT transistor is presented. The suggested model can predict the sheet electron concentration within the transistor channel over the whole voltage operation range. Compared to the existing models, the new model is closed-form analytical that has no discontinuity, which is highly important for the current model convergence. The model satisfies the charge conservation law and present smooth translation from quantization and Fermi statistics to the classical Boltzmann statistics in the flatten band condition. The model is in excellent agreement with the numerical data, 2D TCAD simulation at flatten band conditions and compatible with the SPICE program. The results' analysis confirms the model stability at different temperatures.